Chemical Modification of Cotton Fabrics with Polyhexamethylene Guanidine for Salt-Free Dyeing with Reactive Dyes. Issue 1 (31st December 2023) - Wu, Yanxiu; Niu, Tianjie; Zhai, Xiaolei; Sun, Deshuai; Zhang, Xiaodong; Fang, Long
ABSTRACT: To realize clean dyeing of cotton fabrics, a new modification process was proposed. First, oxidized cotton fabrics were obtained by using 2, 2, 6, 6-tetramethylpiperidin-1-oxyl radical and sodium hypochlorite in the form of selective oxidation. Cationic cotton fabrics were prepared by the Schiff base reaction between polyhexamethylene guanidine and oxidized cotton fabrics. The chemical structure and surface morphology of the modified cotton fabrics were analyzed by Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy, X-ray diffraction and scanning electron microscope. Salt-free dyeing of modified cotton fabrics with four commercial reactive dyes was carried out, which was compared with the raw cotton fabrics dyed in the conventional dyeing. The result revealed that the color fastness of cotton cloth before and after modification was similar. The exhaustion rate and the total utilization of modified cotton fabrics increased by 20–30% and 30%, respectively. At the same time, the fixation rate reached more than 90%. In addition, mechanical properties of modified fabrics could be fully met with the application standard for dyed fabrics.